2022
DOI: 10.15835/nbha50212782
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and heterosis for fiber color and quality in cotton (Gossypium hirsutum L.)

Abstract: The interest in organic cotton (colored) has been increased due to high contamination and environmental pollution during fabric dying process. However, detailed studies are needed to determine the genetic and yield related traits. Eight different cotton genotypes (3 green, 3 brown and 2 white) with known fiber color values were used in the current study to record combining ability and heterosis for fiber colour and quality traits. An 8×8 half diallel hybrid population containing 28 F1 hybrids was analysed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
3
3
0
Order By: Relevance
“…The total genetic variability was partitioned to general combining ability (GCA) and specific combining ability (SCA). The variance due to GCA was lower than SCA for all traits except fibre strength which reflects the preponderance of non-additive types of gene action (dominant or epistatic) controlling these traits, which is in accordance with previous results of Ahuja and Dhayal, (2007), Karademir et al (2009), Tuteja and Verma (2011), Tuteja et al (2013) and Verma et al (2017) and Giri et al (2020). The results are similar to the findings of Rauf et al 2006, Karademir et al (2009, Verma et al (2017) who studied the conventional cross combinations in G arboreum.…”
Section: Resultssupporting
confidence: 91%
“…The total genetic variability was partitioned to general combining ability (GCA) and specific combining ability (SCA). The variance due to GCA was lower than SCA for all traits except fibre strength which reflects the preponderance of non-additive types of gene action (dominant or epistatic) controlling these traits, which is in accordance with previous results of Ahuja and Dhayal, (2007), Karademir et al (2009), Tuteja and Verma (2011), Tuteja et al (2013) and Verma et al (2017) and Giri et al (2020). The results are similar to the findings of Rauf et al 2006, Karademir et al (2009, Verma et al (2017) who studied the conventional cross combinations in G arboreum.…”
Section: Resultssupporting
confidence: 91%
“…Among the testers per se performance IR-3701and followed by FH-113 displayed maximum fibre fineness. The present results are in agreement with those of Hussain et al (2010), Karademir and Gencer (2010), Kumar et al (2016), Feng et al (2011), Rajmani (2014. All the twenty-one F2 hybrids showed positive related heterosis, the highest heterosis displayed by CRIS-342 × VH-291 and VH-292 × FH-113.…”
Section: Dendogram Of Fibre Traits In F1 and F2 Generationsupporting
confidence: 93%
“…indicated that cross Sadori × VH-291 and CRIS-342 × VH-291 gave maximum fiber strength; among female parents per se, VH-259 and VH-292 gave produced maximum fiber fineness, while the testers VH-291 followed by IR-3701 gave maximum fiber strength. The present results are in agreement with those of Hussain et al (2010), Karademir andGencer (2010) Basal et (2011), Kumar et al (2016), Feng et al (2011), Dhivya et al (2014), Rajmani (2014 and Rasheed et al (2014). Among the twenty-one F2 hybrids only seventeen showed positive related heterosis, the crosses Sadori × VH-291 and Sadori × FH-113 displayed highest relative heterosis.…”
Section: Dendogram Of Fibre Traits In F1 and F2 Generationsupporting
confidence: 92%
“…Additionally, Çiçek and Kaynak (2008) reported additive gene effects, while Mohamed et al (2009) documented both additive and non-additive gene effects. Karademir and Gençer (2010) stated that non-additive gene effects were present.…”
Section: Ginning Percentage (%)mentioning
confidence: 99%
“…Cheatham et al (2003) and Murtaza et al (2004) have concluded that both additive and dominant gene effects exist. Karademir (2005), and Karademir and Gençer (2010) found that non-additive gene effects were at work; Minhas et al (2008) found that partial dominance and additive gene effects were important.…”
Section: Fiber Elongation (%)mentioning
confidence: 99%